122 Defining Factors Predictive of Persistent Climacturia after Radical Prostatectomy. (1st May 2022) - Martinez, J Flores; Benfante, N; Schofield, E; Mulhall, JP
ABSTRACT: Introduction: Climacturia (Cl) is defined as the involuntary leakage of urine around the time of orgasm. Cl is a common clinical condition after radical prostatectomy (RP). Cl is a barrier to sexual satisfaction. Rates as high as 60% have been reported with little data on the chronology of recovery. Objective: This study aimed to evaluate the natural history of CI after RP. Methods: Men who underwent RP and completed a proprietary sexual incontinence questionnaire at 12 and 24 months (±3 months) constituted the study sample. Pre or postop ADT or radiation therapy were exclusions. We assessed demographics, comorbidities, baseline testosterone (T), pre-RP prostate specific antigen (PSA), Gleason group, nerve sparing status (NSS), and the presence of stress urinary incontinence (SUI) post-RP. Primary end-point was Cl rate at 12 and 24 months post-RP. Predictors of Cl were analyzed using a series of logistic regression models. Factors entered into the model included age, diabetes, smoking history, baseline T, baseline PSA, Gleason score sum, and NSS score. Results: Data on 152 men were analyzed. Mean age 61±8 years. 45% had hypertension, 60% hyperlipidemia, 10% had diabetes, 18% obstructive sleep apnea, 8% were current smoker, and 27% former smokers. Baseline T and PSA were 421±176 ng/dL and 7±6 ng/mL. The median Gleason score was 7, 82% of patients had bilateral NSS, 13% unilateral. Median NSS score was 3 (IQR 2, 4). Cl prevalence at 12 and 24 months post-surgery were 38% and 39%. No patient characteristics were associated with CI at either 12 or 24 months post-RP. Conclusion: Cl is highly prevalent at 12 months post RP and when present at this juncture appears to be unlikely to recover. Disclosure: Work supported by industry: no.